Kemampuan Perawatan Diri dengan Edukasi Manajemen Penyakit Degeneratif Pada Lansia Di Panti Werdha - Maria Manungkalit; Ni Putu Wulan Purnama Sari; Agustina Chriswinda Bura Mare (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2024)
Aging is a process experienced by every individual with increasing age. It is said to be elderly (elderly) if a person is over 60 years old. In the elderly, health problems will begin to be disrupted as a result of decreased function and changes in body structure so that it will affect the self-care of the elderly. Effective self-care is defined as a sense of responsibility towards oneself in maintaining one's own health. It is hoped that the elderly in dealing with health status problems can identify the symptoms that appear and know what steps and actions must be taken to reduce or reduce their pain. Community service activities carried out at the orphanage using the lecture method (counseling) and question and answer discussions. The activity ran smoothly and was attended by 82 elderly out of a population of 150 elderly people. Before the material is given, participants are first given an activity pretest questionnaire and will be given back with the same leveling as the activity posttest questionnaire to measure the participant's level of understanding of the material presented. The output that has been obtained from the implementation of this activity is shown from the results of increasing the knowledge of the elderly about self-care abilities for most of the elderly after being given health education, the level of knowledge has increased by a percentage of 64.6%. With an increase in the knowledge of the elderly, it is hoped that they will be able to take care of themselves independently or at least care.